Phytochemicals, Traditional Uses and Processing of Aconitum Species in Nepal - Shyaula, Sajan L (Nepal Journal of Science and Technology, 2012)
The tuberous roots of genus Aconitum are commonly applied for various diseases, such as rheumatic fever, painful joints and some endocrinal disorders. It stimulates the tip of sensory nerve fibers. These tubers of Aconitum are used in the herbal medicines only after processing. At the mean time, there remain high toxicological risks of the improper usages of Aconitum. The cardio- and neurotoxicity of this herb are potentially lethal. Some of the species like A. ferox and A. spicatum are deadly poisonous while others like A. oreochryseum and A. bisma are used as the antidote for Aconitum poisoning. It is therefore, a valuable drug as well as an unpredictable toxic material. In the current review, assessments of Aconitum species are carried out, to increase knowledge for the safety uses, in context of Nepal. The traditional uses, phytochemical studies, its processing techniques and toxicological principles are reviewed. DOI: http://dx.doi.org/10.3126/njst.v12i0.6496 Nepal Journal of Science and Technology 12 (2011) 171-178